Corrosion behavior and mechanism of selective laser melted Ti35Nb alloy produced using pre-alloyed and mixed powder in Hank's solution. (15th August 2021) - Qin, P.; Chen, L.Y.; Zhao, C.H.; Liu, Y.J.; Cao, C.D.; Sun, H.; Zhang, L.C.
Highlights: Selective laser melted Ti35Nb was produced by mixed (-M) and pre-alloyed powder (-P). Corrosion behavior of Ti35Nb-M and Ti35Nb-P was investigated in Hank's solution. Heterogeneous oxide films distinctly form on the TiNb and Nb regions in Ti35Nb-M. Both types of samples have double-layered oxide films in TiNb regions. Ti35Nb-M has inferior outer loose layer compared with Ti35Nb-P. Abstract: This work investigated the corrosion behavior and mechanism of selective laser melted (SLM) Ti35Nb separately using mixed powder (Ti35Nb-M) and pre-alloyed powder (Ti35Nb-P) in Hank's solution. Both types of samples demonstrate similar corrosion behavior, and double-layered oxide films form on the TiNb regions in both Ti35Nb-M and Ti35Nb-P. However, Ti35Nb-P has more stable oxide films than Ti35Nb-M because the outer porous oxide layer formed on Ti35Nb-P has smaller thickness and less defects according to Mott-Schottky analysis. Distinct oxide films also form on the TiNb and Nb regions in Ti35Nb-M due to unmelted Nb particles.